Addressing low technical competency of fund accounting specialists of Trades Reconciliation Group: An action research on professional advancement through training and development - Gerosanib, Arlien V. (Animo Repository, 2018)
In this action research, our group focused on addressing an issue that we collaboratively identified, which is low level of technical competency of Fund Accounting Specialist in Trades Reconciliation Group. Technical competencies reflect skills, know-how and processes needed to deliver the organizations core business operations and services (Mohammed, 2010). Manifestations of this issue include revisions and additional review due to inadequate analysis; over reliance to Subject Matter Experts (SME) that exposed to Key-man Risk and inability to meet the Scorecard Metric target. In this project, we aimed to: (1) equip members of our group with the required knowledge for technical competency (2) improves our scorecard metrics (3) reduce over reliance on subject-matter experts of the group. Our goal in this research is to enhance a true culture of service excellence by making our human resources as sustainable competitive advantage for the firm. I used several frameworks which were applicable in addressing our issue. I was guided by Kalamas and Kalamas Gap Analysis, Fisher et al.s Training Cycle and Kirkpatricks Four-level Training Evaluation Model. We applied Hiatts ADKAR Model to implement change in the organization. The interventions we implemented to address the issue on are: (1) conducting technical training to strengthen the competency level of Fund Accounting Specialists, and (2) Knowledge Sharing Sessions. These interventions were successful in achieving the objectives, and the importance of open communication was highlighted in addressing the issue. The experience taught me the importance of teamwork, commitment, and respect for different ways of thinking and the contribution of others. I have also observed positive changes in my colleagues, such as increase in motivation, confidence, and creativity. This project materialized because of collaboration and valuable contributions of the members of our group. The most rewarding part of this project was being a change agent in my own organization. For the next cycle, I recommended having a Career Management Program to further strengthen the Fund Accounting Specialists technical competency. A well-designed career development system enables organizations to tap their wealth of in house talent for staffing and promotion by matching the skills, experience, and aspirations of individuals to the needs of the organizations (Patrick & Amit , 2011).